Synthesis of Ordered Bimodal Mesoporous Silica Nanoparticles from as Synthesized MCM-48 - TIAN, DONG; ZHAO, XING (Asian Journal of Chemistry, 2010)
The convenient preparation of ordered bimodal mesoporous silica nanoparticles has been achieved by mild-temperature post-synthesis hydrothermal treatment of as-synthesized MCM-48 mesoporous materials in H2O2 solution. X-ray diffraction, TEM, FT-IR, TGA and nitrogen sorption were used to characterize the obtained bimodal mesoporous silica sample. The bimodal mesoporous MCM-48 can be obtained only under H2O2 hydrothermal treatment. Hydrogen peroxide plays an important role in simultaneously removing organic templates and forming ordered bimodal mesopores.